Analysis and Design of Controller for Level Process Control without Sensor - Muhasain, Zaid Abed Aljasim; Muhasain, Saif Abed Aljasim (Nahrain University College of Engineering Journal, 2010)
This paper deals with process control, generalized definition and modeling design of flow systems and control it based on compare to constant as principle of operation approach. After reviewing the operation of the plant, a compare system between water level and desire level is formulated to control flow rate. The scheme is then designed and tested by Matlab and Simulink Toolbox. Simulation is presented and shown that on/off switch with constraint is better and moreversatile compare with conventional approach.